Critical development factors in hybrid libraries - Silva, Rafaela Carolina da [UNESP]; Martins Damian, Ieda Pelogia [UNESP]; Caldas, Rosangela Formentini [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2020)
When a library converges it goals to the environment in which it is inserted, it is understood that it is moving to be hybrid. Understanding Knowledge Management as a mix of new and traditional ideas, which involves culture, technology, communication and individuals, hybrid libraries work with it. From this perspective, this research aims to identify the critical success factors for Knowledge Management in hybrid library's environment. The study has qualitative approach, and exploratory type, preceded by a literature review, and permeated by the Case Study method. The results showed people, technology, knowledge sharing, and environment are critical success factors for the development of organizational culture in hybrid libraries. These factors can be implemented following organizational diagnosis guidelines, improvement plan, interdisciplinary meeting, library identify, selection of technology, and implement/adjustment of services. It concludes the critical success factors for Knowledge Management in hybrid libraries involve user training, employee training, types of existing technologies and their distribution to library members and employees, libraries in the lives of their communities, ways of developing communities, and integration between institutions.
Keywords: Hybrid libraries; Critical success factors; Knowledge Management